2022
DOI: 10.1098/rstb.2021.0012
|View full text |Cite
|
Sign up to set email alerts
|

The role of phenotypic plasticity in the establishment of range margins

Abstract: It has been argued that adaptive phenotypic plasticity may facilitate range expansions over spatially and temporally variable environments. However, plasticity may induce fitness costs. This may hinder the evolution of plasticity. Earlier modelling studies examined the role of plasticity during range expansions of populations with fixed genetic variance. However, genetic variance evolves in natural populations. This may critically alter model outcomes. We ask: how does the capacity for plasticity in population… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 106 publications
(158 reference statements)
0
48
0
Order By: Relevance
“…This assumption is supported by a recent study that explores inter and intraspecific variation of cuticular hydrocarbons (which determine the waterproofing capacity of the cuticle) in Enochrus species (Botella-Cruz et al, 2019). Furthermore, it has been suggested that physiological plasticity (Terblanche & Hoffmann, 2020), and plastic desiccation responses in particular (Kellermann et al, 2020), might have a limited impact on species distributions, perhaps due to its associated fitness costs (Eriksson & Rafajlović, 2022).…”
Section: Non-aridity-relatedmentioning
confidence: 89%
“…This assumption is supported by a recent study that explores inter and intraspecific variation of cuticular hydrocarbons (which determine the waterproofing capacity of the cuticle) in Enochrus species (Botella-Cruz et al, 2019). Furthermore, it has been suggested that physiological plasticity (Terblanche & Hoffmann, 2020), and plastic desiccation responses in particular (Kellermann et al, 2020), might have a limited impact on species distributions, perhaps due to its associated fitness costs (Eriksson & Rafajlović, 2022).…”
Section: Non-aridity-relatedmentioning
confidence: 89%
“…Plasticity can extend the range of environments allowing population persistence and thereby facilitate range expansion—another indirect evolutionary consequence of temporal variation. Erikkson & Rafajlović explore this interplay between temporal variation and the evolution of plasticity at range margins [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the model, the fitness of individual k in deme i in generation τ was assumed to depend on the phenotype of the individual, the locally optimal phenotype ( θ ( i ) ), the local population size and (potentially costly) plasticity (Eriksson & Rafajlović, 2022): In equation (2), the term stands for the relative reduction in fitness due to the direct cost of plasticity, i.e., it does not include any fitness reduction due to potential maladaptive plasticity (hereafter this term is referred to as the cost-related function). The effect of maladaptive plasticity on fitness is accounted for by the last term of equation (2).…”
Section: Methodsmentioning
confidence: 99%